Production Technique of Female Tilapia (Oreochromis niloticus) Brood Stock at Verification Level Functional Male (XX) - Tristiana Yuniarti; Sofi Hanif; Teguh Prayoga; Suroso Suroso (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2009)
A technology for producing tilapia monosex female brood stock was needed in order to fulfill the female brood stock for YY male brood stock. The first step was producing XX male brood stock. A monosex female brood stock generation could be obtained if XX male brood stock population was mated with the female. The objective of this activity was to obtained XX male brood stock veryvication result. The result showed that 2 XX male were obtained from 38 fungtional male brood stocks. This could be seen that from female offspring > 95% only 2 brood stocks, i.e. brood stock code 460041352B qnd 460966737A Key word: Tilapia, breeding programe, sex reversal, female offspring